2022
DOI: 10.31586/ojer.2022.305
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement in the Academic Performance of Students in Ghana: Socio-Economic Status

Abstract: The purpose of the study was to assess the socioeconomic status and levels of parental involvement on the academic performance of Junior High School Students in the Upper West Akim District in Ghana. The study adopted the quantitative approach and specifically used the descriptive survey design. Simple random sampling and purposive sampling techniques were used for the selection of schools and respondents for the study. The main instrument used for data collection was questionnaire. The Statistical Product and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
2
3
0
1
Order By: Relevance
“…The survey also found that parents are under-empowered and do not assist their children with their schoolwork, which has a negative impact on their children' learning outcomes. These findings corroborate what Kwarteng et al (2022) found in their study that assessed the socioeconomic status and levels of parental participation on the academic performance of junior high school students in Ghana. The descriptive survey design was utilized expressly as part of the study's quantitative methodology.…”
Section: Parental Involvement In Students' Academic Achievementsupporting
confidence: 90%
See 1 more Smart Citation
“…The survey also found that parents are under-empowered and do not assist their children with their schoolwork, which has a negative impact on their children' learning outcomes. These findings corroborate what Kwarteng et al (2022) found in their study that assessed the socioeconomic status and levels of parental participation on the academic performance of junior high school students in Ghana. The descriptive survey design was utilized expressly as part of the study's quantitative methodology.…”
Section: Parental Involvement In Students' Academic Achievementsupporting
confidence: 90%
“…This is because, academic achievement of the students and the parents' educational background are closely correlated since raising children's mathematical abilities heavily relies on the parents' self-assurance in encouraging the growth of their children's arithmetic knowledge and skills. This is confirmed by Kwarteng et al (2022) study's and Kafoussi et al (2020) study's findings. Kwarteng et al in their study came to the conclusion that a significant element influencing students' academic performance is their socioeconomic status, specifically their education, employment, and income levels.…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 78%
“…Interés de los padres en los asuntos relacionados con lo que estoy estudiando en la escuela Básicamente, la falta de implicación de los padres en el bienestar de sus hijos contribuye enormemente al bajo rendimiento de los alumnos (Kwarteng et al, 2022). Hay un proverbio que dice "puedes llevar un caballo al río, pero no puedes obligarlo a beber".…”
Section: Involucramiento De Los Tíosunclassified
“…According to research conducted on virtual school learning settings before the flu outbreak, parents can serve as learning coaches for children who spend most of their day online. Teacher responses revealed that parental scaffolding is particularly useful for online learners: arranging and managing learners' schedules, developing relationships and interactions, monitoring and stimulating learner involvement, and instructing learners as needed (Albulescu et al, 2023;Kwarteng, et al, 2022;Leithwood et al, 2020).…”
Section: Job Satisfaction and Learner's Academic Performancementioning
confidence: 99%